IS AN EXTERNAL FOCUS OF ATTENTION MORE BENEFICIAL THAN AN INTERNAL FOCUS TO BALL CATCHING IN CHILDREN? (Kinesiology, 2017)
The performance benefits of adopting an external relative to an internal focus of attention have been demonstrated for many different targeting and balance tasks. No study has examined attentional focus effects for interceptive motor skills. Also, the majority of studies have used adult participants. In this study, children (mean age: 8.75 years, SD=0.79; 15 girls, 9 boys) were required to catch tennis balls in the frontal plane under the external focus (EF), internal focus (IF), and control (Cont) conditions. Participants were asked to stand behind a yellow line (2 × 100 cm), 15 m apart from a tennis ball throwing machine. In a within-participant design, participants performed 10 trials under each IF (“concentrate on your hands”), EF (“concentrate on the ball”), or Cont (no focus instructions) conditions. The order of conditions was counterbalanced. Performance data were analyzed using a one-way analysis of variance (ANOVA) with repeated measures on attentional focus conditions (internal, external, and control) (alpha=.05). Catching performance was significantly different and more effective in the EF (M=1.53, SD=0.25) than in the IF (M=1.39, SD=0.35) condition, while both EF and IF were not significantly different from the Cont (M=1.49, SD=0.28) condition. The current findings suggest that the external focus of attention is more beneficial, compared to the internal focus, to motor performance of an interceptive skill in children.Key words: attentional focus, instructions, motor performance, interceptive skills